PENGARUH KEPEMILIKAN MANAJERIAL DAN CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP TAX AVOIDANCE DENGAN KOMISARIS INDEPENDEN SEBAGAI VARIABEL MODERASI - Ulhaq, Afifah Dhia; Efendri, Efendri (TRILOGI ACCOUNTING & BUSINESS RESEARCH, 2024)
The study aims to examine the effect of managerial ownership and corporate social responsibility of tax avoidance with independent commissioners as a moderation variable. The sample used in this research was 276 manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2017-2021 period. The sample selection technique uses purposive sampling and the data used is secondary data obtained from the Indonesian Stock Exchange (BEI). Data analysis uses Multiple Linear Regression analysis. Based on the research results, it proves that Managerial Ownership and Corporate Social Responsibility influence Tax Avoidance. The moderating variable Independent Commissioner is unable to moderate the influence of Managerial Ownership on Tax Avoidance, while the Independent Commissioner moderates the influence of Corporate Social Responsibility on Tax Avoidance.Keywords: Managerial Ownership, Corporate Social Responsibility, Independent Commissioners, Tax Avoidance